Low body mass index increases risk of anemia in patients with HIV-AIDS receiving antiretroviral therapy - Widiyanti, Mirna; Ubra, Reynold; Fitriana, Eva (Faculty of Medicine, Trisakti University, 2017)
BackgroundIn acquired immunodeficiency syndrome (AIDS) cases, cytopenias of all major blood cell lines were increasingly recognized in patients with HIV infection. Anemia commonly occurs during HIV infection and has been associated with increased progression to AIDS and decreased survival. The aim of this study was to determine the prevalence of anemia and associated risk factors in adults with HIV-AIDS receiving antiretroviral therapy (ART). MethodsA cross sectional study was conducted involving 90 adults with HIV-AIDS. Sociodemographic data were collected using a questionnaire. In all patients, CD4+ lymphocyte counts were performed by means of a PIMA analyzer, while hemoglobin was determined using a Sysmex hematology analyzer. The WHO cutoff value of hemoglobin was adjusted to altitude to define anemia. Mild to moderate anemia was defined as hemoglobin 8-13 g/dL for men and 8-12 g/dL for women. Severe anemia was defined as hemoglobin 8 g/dL. Data was analyzed by using logistic regression test.ResultsThere were 90 subjects with HIV-AIDS in this study. Anemia was found in 50 subjects (55.6%), consisting of 12.2% with mild anemia and 43.4% with moderate to severe anemia. Multiple logistic regression showed that an important risk factor for anemia was low body mass index (BMI) between <17-18.5 (OR=4.20; 95% CI=1.23-14.36). However, the CD4 <350 cells/mm3 was not a significant risk factor for anemia (OR=1.03; 95% CI=0.21-5.04).ConclusionsLow BMI increases the risk of anemia in subjects with HIV receiving ART. Better screening for anemia and infectious diseases, and modified harm reduction strategy for injection drug users are primary needs in HIV patients.